A METHOD OF DESIGNING THE MIXING ZONES OF A BUBBLE EXTRACTOR - Ikromjon Karimov; Ilkhomjon Majidov (American Journals Publishing, 2023)
In the article, theoretical studies were carried out to determine the dimensions of the newly created bubble extractor that ensure the operation of the internal and external mixing zones in the hydrodynamic mode of equal speed, and an equation was derived that determines the diameter of the external mixing zone depending on the gas velocity and gas volume. As a result, an opportunity was created to determine the number of contact elements and overall dimensions in creating an industrial version of the device, depending on the performance of the device.
Keywords: Bubble extractor, inner zone, outer zone, mixing, gas cushion, liquid velocity, gas content, coefficient, gas transfer holes.